(untitled) (Cadernos de Sociomuseologia, 2026)
In line with the new definition of museums proposed by ICOM, which highlights educational experiences and knowledge sharing as an important objective for museums, and with the focus of the annual ICOM 2025 conference, which places youth empowerment and participation as strategic priorities, it is clear that teacher training plays a key role in promoting these aspects during the educational visits they take with their students. This article investigates the mediation models and levels of youth participation that appear in educational proposals for museum visits developed by 29 science teachers in training in Chile, after a training intervention and an exploratory visit to a science museum in the country. The qualitative-interpretative analysis coded each activity and summarized the mediation model (focused on the educator, the visitor or the exhibition) and the predominant levels of youth participation. The results show that visitor-centered mediation is still rare. Likewise, the most common levels of participation are symbolic consultation and shared decision-making, and no instances of youth leadership were found in any sequence. Based on the above, we propose some discussions around teacher training to enhance museum experiences geared towards youth agencies, particularly in the case of science museums and their links to local and global socio-scientific issues. Keywords: Science museums; youth participation; non-formal education; teaching and learning sequences; teacher training in museums